2016
DOI: 10.1155/2016/4369574
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus and Malignancy after Solid Organ Transplantation: A Clinical Update

Abstract: Malignancy after solid organ transplantation remains a major cause of posttransplant mortality. The mammalian target of rapamycin (mTOR) inhibitor class of immunosuppressants exerts various antioncogenic effects, and the mTOR inhibitor everolimus is licensed for the treatment of several solid cancers. In kidney transplantation, evidence from registry studies indicates a lower rate of de novo malignancy under mTOR inhibition, with some potentially supportive data from randomized trials of everolimus. Case repor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 101 publications
(121 reference statements)
1
35
0
3
Order By: Relevance
“…A specific azathioprine signature mutation has recently been identified in cSCC (47); procarcinogenic mechanisms for the calcineurin inhibitor, cyclosporine, include reduced UV DNA damage repair (48), reduced apoptotic response to UV (49), and ATF3 induction and suppression of p53-dependent senescence (48,50). In contrast, mTOR inhibitors are associated with reduced cSCC risk, possibly through both antiproliferative and antiangiogenic properties (34,(51)(52)(53) and the risk associated with newer immunosuppressive drugs, including tacrolimus and mycophenolate, may also be reduced, but supportive epidemiologic data are not yet established (54,55). Voriconazole, an antifungal agent commonly used in transplantation, has direct photocarcinogenic effects (56) and is associated with significantly increased risk of aggressive cSCC (57).…”
Section: Immunosuppressionmentioning
confidence: 99%
“…A specific azathioprine signature mutation has recently been identified in cSCC (47); procarcinogenic mechanisms for the calcineurin inhibitor, cyclosporine, include reduced UV DNA damage repair (48), reduced apoptotic response to UV (49), and ATF3 induction and suppression of p53-dependent senescence (48,50). In contrast, mTOR inhibitors are associated with reduced cSCC risk, possibly through both antiproliferative and antiangiogenic properties (34,(51)(52)(53) and the risk associated with newer immunosuppressive drugs, including tacrolimus and mycophenolate, may also be reduced, but supportive epidemiologic data are not yet established (54,55). Voriconazole, an antifungal agent commonly used in transplantation, has direct photocarcinogenic effects (56) and is associated with significantly increased risk of aggressive cSCC (57).…”
Section: Immunosuppressionmentioning
confidence: 99%
“…(9) The mammalian target of rapamycin (mTOR) inhibitor everolimus (EVR) offers an alternative immunosuppressant to CNIs, with the potential to reduce CNI-related nephrotoxicity without loss of efficacy (10) and possibly to lower the risk of posttransplant malignancies. (11) The randomized H2304 study demonstrated that EVR with reduced TAC was associated with significantly better renal function and comparable efficacy over the first 3 years after liver transplantation compared with standard TAC therapy. (12)(13)(14) The recent SIMCER trial examined the use of EVR in combination with mycophenolic acid (MPA) to support a CNI-free regimen early after liver transplantation.…”
mentioning
confidence: 99%
“…Besides, the effect of other immunosuppressive agents provided a neutral effect on the occurrence of postrenal transplantation malignancy. Although clinical trials provided the safety and efficacy of monotherapy with mTOR inhibitor after transplantation, most patients in Taiwan received combination therapy as maintenance therapy. Further studies on the effect of combination therapy may be considered to find out the optimal regimen in transplantation recipients.…”
Section: Discussionmentioning
confidence: 99%